Scale insects (Hemiptera, Coccomorpha: Diaspididae, and Pseudococcidae) found on Myrciaria dubia in Pará State, Brazil - Noronha, Aloyséia C. S.; Wolff, Vera R. S.; Silva, Vitor C. P.; Santos, Ruth H. S.; Kaydan, Mehmet B.; Nascimento, Walnice M. O.; Gurgel, Fábio L. (Entomological Communications, 2023)
The present study aimed to report the occurrence of scale insects, namely Chrysomphalus aonidum (Linnaeus, 1758), Ischnaspis longirostris (Signoret, 1882), Pinnaspis aspidistrae (Signoret, 1869) (Hemiptera: Diaspididae), and Nipaecoccus filicis Williams & Granara de Willink, 1992 (Hemiptera: Pseudococcidae) on plants of Myrciaria dubia (Kunth) McVaugh (Myrtaceae) in the experimental fields of Embrapa Amazônia Oriental in the municipalities of Belém and Tomé-Açu, Pará State, Brazil. This is the first report of these species on M. dubia, as well as of N. filicis in Brazil.